Potential Mechanisms of Acupuncture for Functional Dyspepsia Based on Pathophysiology - Yang, Na-Na; Tan, Chun-Xia; Lin, Lu-Lu; Su, Xin-Tong; Li, Yue-Jie; Qi, Ling-Yu; Wang, Yu; Yang, Jing-Wen; Liu, Cun-Zhi (Frontiers in Neuroscience, 2022)
Functional dyspepsia (FD), a common disorder of gastrointestinal function, originated from the gastroduodenum. Although the therapeutic effect of acupuncture has been investigated by various high-quality randomized controlled trials, the potential mechanisms showed obvious heterogeneity. This review summarized the potential mechanisms of acupuncture on FD in order to guide for future both laboratory and clinical studies. Here, we argued that the primary cause of FD was gastroduodenal low-grade inflammation and acid exposed, which impaired mucosal integrity, caused brain-gut axis dysfunction, and impaired brain network connectivity, all of which generated various symptom patterns. Overall the clinical studies indicated that acupuncture was a promising treatment to alleviate symptoms of FD patients, whose efficacy was influenced by acupoints and individual variance. Mechanistically, studies with animal models of FD and patients have shown that acupuncture, a non-invasive strategy for nerve stimulation, may have the potential to control intestinal inflammation and suppress acid-secretion via different somatic autonomic reflex pathways, regulate the brain-gut axis through intestinal microbiota, and so has the potential to ameliorate FD-symptoms. The cumulative evidence demonstrated that acupuncture is a promising treatment to alleviate symptoms of FD patients, involving a combination of several mechanisms.